أثر حوكمة المؤسسات على إدارة الصفقات العمومية: دراسة حالة مؤسسة اتصالات الجزائر فرع الاغواط - بريشي مصطفى جمال الدين; بدرينة مراد (جامعة عمار ثليجي -الأغواط, 2022)
This study aimed to highlight the impact of corporate governance on managing public procurement and this in light of the efforts aimed at developing and improving the organization of managing public deals and preserving public money, This study concluded that there is a high level of corporate governance and public procurement management in the The Algerian communications in Laghouat, and that there is an impact of corporate governance in its dimensions (disclosure, transparency, accountability, justice, responsibility) on the management of public deals in the The Algerian communications in Laghouat. Key words: corporate governance, management of public deals, Case Study The public treasury in Laghouat.